A Study of the Implementation of Speaking English Skill at Dormitory Attanwir Language Center - Moch Wahyudi Utomo (Graduate Program, University of Islam Malang, 2021)
This study was aimed at examining the teaching speaking process at Attanwir Language Center. This study employed a qualitative method: a case study utilized to study a phenomenon in real life comprehensively, yet such an understanding entailed pivotal contextual conditions since they tremendously had relevancy to the phenomenon of study. The data were attained through observation, questionnaire, and interview. The data were subsequently analyzed to attain triangulation data. It was grounded on literature; it was not statistic. The results of this study indicated that in conveying the materials for the learners, Direct method was mostly utilized for the process of teaching speaking at The Attanwir Language Center (ALC). Besides, the materials were not really arduous since natural conversations were prioritized. Meanwhile, there were some hindrances that occurred during the teaching speaking. For instance, it was hard to arrange and attend a regular meeting between the learners and the teacher. Additionally, they frequently ran out of the conversation topics in the circle. The result also demonstrated that most of the members coming to Attanwir Language Center (ALC) enjoyed learning English and practicing their speaking skill due to the fact that they were given different method, flexible time, and distinctive environment.